Animal Husbandry and Ritual at Vrčevo Hillfort in the Bronze and Iron Ages (Archaeologia Adriatica, 2022)
The paper presents the results of the zooarchaeological analysis of osteological remains of domestic and wild animals from Vrčevo hillfort in Ravni Kotari. The samples were collected in the 2012 archaeological excavations when several occupation layers were defined as evidenced by the finds of floors and hearths. The finds, as well as the results of the first radiocarbon analyses confirmed the continuity of the settlement from the Middle Bronze Age until the end of the Early Iron Age and the beginning of the Late Iron Age. The results of the zooarchaeological analysis indicated that both periods were characterized by continuity in sheep and goat breeding while possible change was evident in cattle breeding. It seems that dogs had special importance for the Bronze Age community as suggested by ritual practice.